PENGARUH KOMITMEN PEGAWAI DAN BUDAYA ORGANISASI DI DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN MUSI RAWAS - Yulpa Rabeta (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
This research was conducted with the aim to find out: a. Does the commitment of employees partially affect the performance of employees in the Department of Manpower and Transmigration of Musi Rawas Regency. b. Does the organizational culture partially influence the performance of employees in the Department of Manpower and Transmigration of Musi Rawas Regency. c. Does employee commitment and organizational culture simultaneously influence the performance of employees in the Manpower and Transmigration Office of Musi Rawas Regency. The results of testing with IBM 17.0 For Window SPSS program conducted: a. Tcount value obtained was 3,291 which was greater than ttable 2,018. Thus, employee commitment variable has a significant effect on employee performance in the Manpower and Transmigration Office of Musi Rawas Regency. b. Tcount value obtained was 3.805 greater than ttable 2,018. Means that organizational culture variables have a significant effect on the performance of employees in the Department of Manpower and Transmigration, Musi Rawas Regency. c. Employee commitment and organizational culture simultaneously influence the performance of employees in the Manpower and Transmigration Office of Musi Rawas Regency. This is evidenced by the calculated Fcount value of 11,413 which is greater than Ftable 3.23 that simultaneously the independent variable (ie employee commitment and organizational culture) has a significant influence on the dependent variable, namely employee performance.